Wear contact problem for a cylindrical sliding bearing under boundary friction - Диха, О.В. (Problems of Tribology, 2016)
Dykha O.V. Wear contact problem for a cylindrical sliding bearing under boundary frictionConducted the solution of the direct wear of the contact problem for a cylindrical bearing. In the calculation of the shaft was made tight and not wore out, the bushing was made hard, and wore out. For engineering estimates of the maximum wear amount from the path of friction (developments) contact pressure was determined from the average values. For the base model the wear resistance was taken to be the dimensionless complex of determining factors: pressure, sliding speed, friction coefficient, viscosity, hardness of the material, the geometric parameters. According to the obtained formula for the calculation of wear in the bearing numerical implementation.Keywords: the cylindrical sliding bearing, wear contact problem, the path of friction, the contact pressure.